THE PRACTICE OF DIGITALIZATION OF EVALUATION ACTIVITIES AND THE PROSPECTS OF ITS APPLICATION IN UZBEKISTAN - Bobirjon Aktamov (American Journals, 2023)
The article discusses the need to develop the market for appraisal services, which is one of the important infrastructures of a market economy. The digitalization processes taking place today all over the world, the introduction of artificial intelligence in various fields and their impact on valuation activities are revealed. The prospects and practical problems of digitalization of appraisal activities in the Republic of Uzbekistan and the introduction of artificial intelligence in this area are highlighted.
Keywords: Assessment activities, assessment, digitalization, artificial intelligence, digitalization of assessment activities, assessment standards, digital technologies, assessment organizations, qualification certificate.